Play Therapy: Artistry and Destiny and the Subject of our Destiny - Bishop, Jay (Canadian Journal of Counselling and Psychotherapy, 2012)
Employing the notions of Vygotsky, Bruner, Sutton-Smith and Csikszent-mihalyi this paper examines theoretically a millisecond of time in a typical play therapy session. The case of a child's attempt to establish contact with reality in play through the therapist is explored. Questions for theory and practice abound.